2017
DOI: 10.1167/iovs.17-21661
|View full text |Cite
|
Sign up to set email alerts
|

CTG18.1 Expansion in TCF4 Among African Americans With Fuchs' Corneal Dystrophy

Abstract: PurposeStudies of Fuchs' dystrophy have largely focused on individuals of European origin. Characterization of disease among African Americans is required to ensure prognostic factors and therapeutic approaches are applicable across diverse patient populations.MethodsWe assessed all self-reported black and white patients aged older than 40 years at a tertiary care institution with a diagnosis of cataract over a 3-year period for concurrent diagnosis of Fuchs' dystrophy. Affected patients in a longitudinal coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…We further found that FECD frequency was higher in EUR Veterans than in other ancestries, after adjustment for age and sex. This finding agrees with that of Eghrari et al 69 who reported a modest reduction in the incidence of FECD in NHB as compared to NHW patients. In comparison, Mahr and colleagues 25 did not observe a difference in FECD incidence between NHW and NHB patients based on their analysis of U.S Medicare claims.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We further found that FECD frequency was higher in EUR Veterans than in other ancestries, after adjustment for age and sex. This finding agrees with that of Eghrari et al 69 who reported a modest reduction in the incidence of FECD in NHB as compared to NHW patients. In comparison, Mahr and colleagues 25 did not observe a difference in FECD incidence between NHW and NHB patients based on their analysis of U.S Medicare claims.…”
Section: Discussionsupporting
confidence: 93%
“…21,22 Herein we used the PheWAS approach to identify relationships between FECD and other disease phenotypes. Considering prior reports that FECD incidence may be higher in females 4,23,24 and may vary between racial groups 25,26 we incorporated these factors into our analysis and noted that female sex and European ancestry were associated with FECD. Our main finding was that diagnostic codes for multiple ocular and non-ocular conditions were elevated in FECD cases.…”
mentioning
confidence: 99%
“…The association between CTG18.1 repeat length and FECD has now been replicated within numerous multi-ethnic cohorts ( Table 2 ). Regardless of subtle variability in designated expansion thresholds used by ourselves and others (ranging from ≥40 to ≥50 repeats), the highest frequencies of CTG18.1 expansions have consistently been reported in predominantly Caucasian FECD populations including those in the United States (62–79%) ( Eghrari et al, 2017a ; Mootha et al, 2014 ; Vasanth et al, 2015 ; Wieben et al, 2012 ), Germany (77%–79%) ( Foja et al, 2017 ; Okumura et al, 2019a ), United Kingdom (77%) ( Zarouchlioti et al, 2018 ), Czech Republic (81%) ( Zarouchlioti et al, 2018 ), and Russia (72%) ( Skorodumova et al, 2018 ). A lower prevalence was noted in a cohort of Australian FECD patients (51%), but the experimental methods employed in this study were unable to detect large expansions which may have decreased ascertainment rates ( Kuot et al, 2017 ).…”
Section: Genetic Association Of Tcf4 and Fecdmentioning
confidence: 77%
“…Interestingly, the correlation between CTG18.1 expansion and FECD is also striking, although typically lower, in other non-Caucasian ethnic groups investigated to date. This includes African Americans (35%) ( Eghrari et al, 2017a ), Indians (17% and 34%) ( Nanda et al, 2014 ; Rao et al, 2017 ), Japanese (26%) ( Nakano et al, 2015 ), Singaporean Chinese (44%) ( Xing et al, 2014 ), and Thai (39%) ( Okumura et al, 2019c ). Notably, CTG18.1 genotyping studies have consistently identified a bimodal distribution of repeat lengths, with the vast majority of patients typically harbouring repeat sizes of <30 or >50 ( Zarouchlioti et al, 2018 ).…”
Section: Genetic Association Of Tcf4 and Fecdmentioning
confidence: 99%
“…Female sex and advanced age are established risk factors. Risk may also differ across populations; lower rates of FECD diagnosis have been observed in African Americans in both clinical settings 17 and Medicare claims 18 .…”
Section: Introductionmentioning
confidence: 99%